IDENTIFICATION OF NATIONAL AND INTERNATIONAL REGULATIONS ON ACCOUNTING DEPRECIATION OF TANGIBLE FIXED ASSETS - Lumbo Flavio MUCOMO (SEA: Practical Application of Science, 2016)

(untitled)
Amortization is the process of gradual recovery of the financial result in irreversible impairment of assets, charges for the year by including the depreciation of the consideration of the duration determined by the projected operating assets, as amortization. Impairment occurs as a result of their use within the entity, or due to the passage of time and the amount of this distribution is performed impairment on the value of new products, works, services or activities carried out using these tangible assets. This process of distribution requires that the conclusion of the economic circuit through profit distribution, works, services or activities harnessed to separate or recover from revenue from that part of the value that was included in the operating cost of title reduction in value. Such amortization is considered separately in depreciation fund which is a power source of the fund's agent economic. Depreciation serves to correct the value of assets to bring to a value closer to reality.